Determination of Biofilm Formation between Different Strains of Propionibacterium acnes Using Biofilm Assay - N., Yusufu, W.; O., Suleiman, H.; Y., Akwa, V.; L., David, D.; A., Taiga (International Journal of Innovative Research in Medical Science, 2019)
Propionibacterium acnes (P. acnes) a member of the normal flora of the skin has constantly been associated with deep tissue infections especially during medical processes. P. acnes have been isolated in deep tissues and are believed to be an aetiological agent in these infections, contributing to the progression of some of these diseases. The biofilm formation ability between different strains of P. acnes was determined. Ten (10) P. acnes clinical isolates were considered, two (2) from acne vulgaris and eight (8) [two (2) per recA types 1A1, 1B, II and III] from lumber herniation tissues. Semi quantitative biofilm analysis using the microtiter plate assay was used with some modification. The semi quantitative biofilm assay was done in triplicates. The result obtained from the biofilm triplicates from 4 days’ incubation using 3 days’ culture showed that isolates 17(IB), 82(IB) and 55(II) showed very high biofilm production for 2 replicates which implies that they are real biofilm producing isolates. Using overnight cultures, higher biofilm production was witnessed with isolates 1(III), Lesion 7 and 84 (IA1) being the highest biofilm producers. Although with 3 days’ culture, isolate 1(III) could easily be discarded as a-non biofilm producer, while lesion 7 and 84 (IA) has been associated to biofilm formation in 3 days’ culture. The production of biofilms by isolates supports the theory that the ability of P. acnes to form biofilms enables it to attach to medical implants hence causing deep tissue infections.